DINAMIKA SOSIAL PERSPEKTIF FILSAFAT PENDIDIKAN ISLAM - JANNA, SITTI RIADIL (ADARA, 2016)
Abstract: A change is a social dynamic that is unavoidable. The social change has a profound influence on Islamic education in its various aspects. This implies that the Islamic education as a social institution must be dynamic and open to changes according locus differences and socio-cultural development of the times. Therefore, although historically Islam has demonstrated its educational dynamic in response to social change, but a lot of the stereotypes that still cling to the typical of Islamic institutional education until now, such as the narrowness of the curriculum, lack of professional educators, and science dichotomy. From here, as a social institution is supposed Islamic education is able to clean itself, which in turn is able to mobilize social change through education that can be viewed through the philosophy of Islamic education Kata Kunci: Dinamika Sosial, dan Perspektif Pendidikan Islam